Tantangan Pendidikan Agama Islam dalam Membentuk Ketahanan Moral Siswa di Era Media Sosial - Nur Anisah Nasution; Indryyani Claudia; Herlini Puspika Sari (IHSANIKA : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the influence of social media on students' moral resilience and to examine the role of Islamic Religious Education (PAI) teachers in addressing the challenges of character building in the digital era. The research employs a qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that social media has a significant impact on students' behavior and morals, particularly in terms of language use, lifestyle, and communication ethics in digital spaces. Low digital literacy has caused some students to be unable to critically filter information, making them easily influenced by trends that are not aligned with Islamic values. PAI teachers face various challenges, such as limited instructional time and the vast access to information available to students. Nevertheless, teachers continue to strive to instill moral values by integrating learning materials with emerging digital phenomena. This study also finds that students' moral resilience can be strengthened through improving digital literacy and fostering collaboration between schools and parents in supervising social media usage.